Pencegahan Penyebaran Covid-19 Melalui Peningkatan Ketahanan Pangan Bagi Warga Terdampak di Surabaya - Susanti Susanti; Anang Kistyanto; Moch Khoirul Anwar; Susi Handayani; Moh Danang Bahtiar; Eka Hendi Andriansyah (Universitas Negeri Surabaya, 2020)
AbstractCovid-19 is a type of virus that can spread through the air. Surabaya occupies the second city in Indonesia with the largest Covid-19 distribution. Solving the Corona virus problem in Indonesia in the form of Social Distancing policy. Limitation of interaction between individuals in all fields. The problem that arises is the difficulty to meeting the needs of the community because of restrictions on activities outside. The purpose of this activity is carried out as an effort to maintain the food security of affected communities so that the community can continue to meet their basic needs. The method used is Mediation, this method is taken to support government policies through social distribution by distributing basic necessities to affected communities Covid-19. The results of the local area communication concluded that the community spent a lot of time at home, bearing in mind the basic needs that had been fulfilled by the basic food aid that had been was given. Through this food aid, it is expected to meet the needs of the community. Without having to meet difficulties in meeting basic needs in order to maintain community immunity and reduce their desire to leave the house shopping for basic needs.Keywords: Covid-19, Food Security, Affected Communities